2014
DOI: 10.1007/s12013-014-0222-z
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Differentiation of Mesenchymal Stem Cells into Neural Stem Cells Using Cerebrospinal Fluid

Abstract: Optimization of a methodology for mesenchymal stem cells (MSCs) differentiation into neural stem cells (NSCs) using cerebrospinal fluid (CSF). MSCs were extracted from umbilical cord blood from healthy, full-term, newborn infants and from the bone marrow of patients. CSF was taken from healthy adult volunteers and patients. Four groups investigated were: A (n = 8) cord blood MSC induced with healthy volunteer CSF (control group); B (n = 7): patient MSCs induced with health volunteer CSF; Group C (n = 12): pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 13 publications
3
23
0
Order By: Relevance
“…Cytokines are commonly used as induction agents because they play a role in promoting stem cell proliferation and differentiation through their own receptors (20). We have demonstrated that hCSF-treated human BMSCs could successfully differentiate into neuron-like cells (10, 11). Three days of hCSF-induction prompts neurite growth, and the cultured cells gradually developed into a tapered, triangular, and irregular shape.…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…Cytokines are commonly used as induction agents because they play a role in promoting stem cell proliferation and differentiation through their own receptors (20). We have demonstrated that hCSF-treated human BMSCs could successfully differentiate into neuron-like cells (10, 11). Three days of hCSF-induction prompts neurite growth, and the cultured cells gradually developed into a tapered, triangular, and irregular shape.…”
Section: Discussionmentioning
confidence: 98%
“…The soma on day 7 was similar to the dendrite and axon-like structures of astrocytes. Compared with cytokine-induced cells, those that were induced with hCSF were quicker to differentiate and which also occurred in higher proportions (10, 11). This has resolved numerous problems associated with the use of culture media and stimulating factors.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations